ECCO Topical Review Optimising Reporting in Surgery, Endoscopy, and Histopathology: Collaboration Between S-ECCO, EduCom, H-ECCO. (11th January 2021) - Adamina, Michel; Feakins, Roger; Iacucci, Marietta; Spinelli, Antonino; Cannatelli, Rosanna; D'Hoore, André; Driessen, Ann; Katsanos, Konstantinos; Mookhoek, Aart; Myrelid, Pär; Pellino, Gianluca; Peros, Georgios; et al.
Abstract: Background and Aims: Diagnosis and management of inflammatory bowel diseases [IBD] requires a lifelong multidisciplinary approach. The quality of medical reporting is crucial in this context. The present topical review addresses the need for optimised reporting in endoscopy, surgery, and histopathology. Methods: A consensus expert panel consisting of gastroenterologists, surgeons, and pathologists, convened by the European Crohn's and Colitis Organisation, performed a systematic literature review. The following topics were covered: in endoscopy: [i] general IBD endoscopy; [ii] disease activity and surveillance; [iii] endoscopy treatment in IBD; in surgery: [iv] medical history with surgical relevance, surgical indication, and strategy; [v] operative approach; [vi] intraoperative disease description; [vii] operative steps; in pathology: [viii] macroscopic assessment and interpretation of resection specimens; [ix] IBD histology, including biopsies, surgical resections, and neoplasia; [x] IBD histology conclusion and report. Statements were developed using a Delphi methodology incorporating two consecutive rounds. Current practice positions were set when ≥ 80% of participants agreed on a recommendation. Results: Thirty practice positions established a standard terminology for optimal reporting in endoscopy, surgery, and histopathology. Assessment of disease activity, surveillance recommendations, advice to surgeons for operative indication and strategies, including margins and extent of resection, and diagnostic criteria of IBD, as well as guidance for the interpretation of dysplasia and cancer, were handled. A standardised report including a core set of items to include in each specialty report, was defined. Conclusions: Interdisciplinary high-quality care requires thorough and standardised reporting across specialties. This topical review offers an actionable framework and practice recommendations to optimise reporting in endoscopy, surgery, and histopathology.